1983
DOI: 10.1073/pnas.80.19.6105
|View full text |Cite
|
Sign up to set email alerts
|

Efficient expression of influenza virus NS1 nonstructural proteins in Escherichia coli.

Abstract: RNA segment 8 of the influenza A virus genome codes for two nonstructural proteins, NS1 and NS2, for which the functions are unknown. Cloned cDNA copies of this gene from three different influenza A virus strains were inserted into an Escherichia coli plasmid expression vector, pASI, carrying the strong regulatable A phage promoter, PL. After induction, the NS1 proteins were overproduced to levels of 20-25% of total cellular protein. This was surprising in that the codon composition for these eukaryotic genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 25 publications
2
63
1
Order By: Relevance
“…Two functional domains of the NS1 protein are required for these nuclear functions: an RNA-binding domain near the amino terminus, and an effector domain in the carboxyl half of the molecule (8). Consistent with these functions, previous studies showed that the NS1 protein is predominantly localized to the nucleus both in infected cells and in cells transfected with the DNA encoding the NS1 protein (12)(13)(14)(15)(16). This nuclear localization is directed at least in part by two separate, independent NLSs in the protein (13).…”
supporting
confidence: 56%
“…Two functional domains of the NS1 protein are required for these nuclear functions: an RNA-binding domain near the amino terminus, and an effector domain in the carboxyl half of the molecule (8). Consistent with these functions, previous studies showed that the NS1 protein is predominantly localized to the nucleus both in infected cells and in cells transfected with the DNA encoding the NS1 protein (12)(13)(14)(15)(16). This nuclear localization is directed at least in part by two separate, independent NLSs in the protein (13).…”
supporting
confidence: 56%
“…1) A polyclonal antiserum raised against a fusion of Gas to the N-terminal 81 residues of the influenza virus NSI protein (34) was used to detect total cellular Gas proteins by Western blot (immunoblot) (data not shown). Protein was undetectable in cells of strain DJ211-3-4 expressing pGALas.…”
Section: Resultsmentioning
confidence: 99%
“…Fusion-tropomyosin was prepared from full-length cDNA clones of rat striated muscle obtained from Dr. B. NadalGinard (Ruiz-Opazo & Nadal-Ginard, 1987), subcloned, and expressed in Escherichia coli using a rat striated muscle a-tropomyosin cDNA (gift of Dr. B. Nadal-Ginard; Ruiz-Opazo & Nadal- Ginard, 1987) that was cloned in pas AEH801 (Young et al, 1983) to produce a fusion protein with 80 amino acids of influenza virus NS1 on the amino terminus (Heald & Hitchcock-DeGregori, 1988;Cho et al, 1990). It was purified and renatured from GuHCl extracts as described earlier (Hitchcock-DeGregori & Varnell, 1990).…”
Section: Methodsmentioning
confidence: 99%